Pengaruh Pemberian Air Kelapa (Cocos nucifera L.) Dan Atonik Terhadap Pertumbuhan Tanaman Cabai Merah Besar (Capsicum annuum L.) - Hasti Maulidya Fassya; Tundjung Tripeni Handayani; Sri Wahyuningsih; Mahfut Mahfut (TECHNO: JURNAL PENELITIAN, 2020)
Large red chili pepper (Capsicum annuum L.) has a fairly complete nutrition and economic value. The supply of large red chili in the country is considered low compared to its demand, that’s why we need to increase its production. Increasing production can be done by fertilizing using natural fertilizers is coconut water (Cocos nucifera L.) and administration of Growth Regulatory Substances (ZPT) is atonik. The purpose of this research is to determine the effect of coconut water and atonic to the growth of large red chilli pepper sprouts determine which consentration of coconut water and atonic that has the most effective effect to the growth of large chilli pepper. This research was conducted in October - November 2019 at the Botany Laboratory, Department of Biology, Faculty of Mathematics and Science, University of Lampung. This research was carried out using a 2x3 factorial design using young coconut water (a) with 3 levels of concentration ie 0% v / v (a1), 25% v / v (a2) and 50% v / v (a3) and atonic solution ( b) with 2 concentrations, namely 0% v / v (b1) and 10% v / v (b2). Data analysis is the data homogeneous first with the Levene test at 5% significance level. Data analysis using analysis of variance (Analysis Of Variance) ɑ = 5%. If the interaction between the two factors is real, then proceed with the determination of the simple effect of coconut water at each level of atonic concentration with the F test at 5% significance level. The results of this research shows that the use of atonic and coconut water effects the growth of large red chili plants, and the most effective concentration to the growth of large red chilli pepper plants is the combination of 0% coconut water + 10% atonic.